ANIMAL NAMES,HABITATS AND ENDANGERED SPECIES. (Ustozlar uchun, 2026)
The conservation of biodiversity has become one of the most urgent global challenges in the 21st century. This study explores the diversity of animal species, their natural habitats, and the growing threat of extinction affecting wildlife populations worldwide. Animals play a crucial role in maintaining ecological balance, yet many species are increasingly endangered due to habitat destruction, climate change, pollution, and human activities.The research examines various animal groups across terrestrial, aquatic, and aerial ecosystems, highlighting how habitat loss directly impacts species survival.